Etiology Of ADHD: Perinatal Hypoxic Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Recent evidence pointing to a disturbance of function of the striatum in attention deficit hyperactivity disorder (ADHD) is reviwed from the Department of Pediatric Neurology, The John F Kennedy Institute Glostrup, Denmark.